EU Polar Cluster ... - Couser, Griffith; Strobel, Anneli; Biebow, Nicole (Zenodo, 2024)
Griffith Couser from European Polar Board and Anneli Strobel with Nicole Biebow from Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research delivered a presentation on ‘EU Polar Cluster’. This presentation was given at the SO-CHIC and OCEAN:ICE Joint Project Conference on the 25th of October 2023 during the ‘Coordination of Field Work/Modeling across Existing Projects’ session. ...